IMPLEMENTASI PENDIDIKAN VOKASI DI SULAWESI BARAT - Nurhalia Nurhalia; Muh Restu; Akin Duli; Rahmadanih Rahmadanih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
This study aims to evaluate the implementation of the Independent Curriculum in SMK in West Sulawesi Province, with a focus on the integration of local potential, utilization of technology, and external cooperation. The method used is a combination of questionnaires and in-depth interviews. Questionnaires were distributed to school principals to collect quantitative data on curriculum implementation, while in-depth interviews were conducted to obtain more in-depth qualitative information on the challenges and strategies faced in implementing the curriculum. The results of the study indicate that most SMK have adopted the Independent Curriculum, which provides flexibility in developing teaching materials according to local potential and the needs of the world of work. However, the challenges faced include limitations in exploring local resources, minimal support from external agencies, and the less than optimal implementation of the local content curriculum. The majority of schools have integrated local potential into learning, although it is not structured evenly. Field practices and projects based on natural resources have been implemented, but are limited by time, resources, and support from industry partners. The use of technology and AI has begun to be implemented, but is hampered by digital infrastructure and technological literacy. External cooperation with industry and research institutions is still limited, so stronger formal partnerships are needed.